QUANTIFICATION OF SUSPENDED SOLID TRANSPORT IN ENDJA WATERCOURSE [DEHAMECHA BASIN-ALGERIA] - TAMRABET, Zeyneb; MAROUF, Nadir; REMINI, Boualem (GeoScience Engineering, 2019)
The Dehamecha watershed is one of the most degraded basins in Algeria. This basin suffers from strong water erosion, especially during floods, where sediments are transported by the Endja watercourse draining it and depositing them in Beni-Haroun dam. Based on data series provided by the National Water Resources Agency of Constantine concerning the Tassadane gauging station, a correlation is made between two data pairs: suspended material concentrations and liquid flow C-Ql, solid flow and liquid flow Qs-Ql. On a monthly scale, the exponential model is the most suitable for the first correlation and the power model for the second one. Based on these two mathematical models, the quantitative estimation is obtained by identifying the average specific erosion rate over a 30 years’ period, which exceeded 1000 tons / km2.year. The extreme events (floods) have a predominant role in the export of large sediment volumes. Keywords: Erosion, suspended solids transport, Endja, Dehamecha watershed DOI 10.35180/gse-2019-0025